IMPLEMENTASI KEBIJAKAN PENDIDIKAN DAN PELATIHAN KEPEMIMPINAN TINGKAT IV DI BADAN KEPEGAWAIAN DAERAH KOTA PALU - Melandari, Ajeng Nurasih (Katalogis, 2016)
This study aims to determine the implementation of Level IV Leadership Training and Education Policy in Regional Employment Board of Palu City. The type of research used in this study was qualitative descriptive research. Informants in this study amounted to 6 people consisting of 1 Head of Training and Education Division,2 Heads of Subdivisions, 2 Field Person-in-Charge ,and 1 Participants ofLevel IV Leadership Training and Education. The types of data were primary and secondary data. Data were collected by means of interview, documentation, and triangulation techniques. Analysis of data used in this studywas Miles and Huberman Model, i.e. data reduction, data presentation, and conclusion. The theory used in this studywas the theory of Edward III consisting of four aspects: communication, resource, disposition/attitude, and bureaucratic structure. The result shows that:first, the communication aspect had not been effective, forthe obstacles in the communication of the committee to the participants was still in frequent. Second, the resource aspect had not already been adequate,neither resources of officers, facilities,or infrastructures. Third, the disposition aspect had not run as expected, for lack of the implementors’ awareness to remain on policy goals. Fourth, the absence of operational standards and procedures (OSP) regardingLevel IV Leadership Training and Education. Thus, the researcher concludes that the implementation of Level IV Leadership Training and Education had not been effective as expected.